AIMETA 2005. Atti del XVII Congresso dell'Associazione italiana di meccanica teorica e applicata. Firenze, 11-15 settembre 2005 - Borri, Claudio; Facchini, Luca; Federici, Giorgio; Primicerio, Mario (Proceedings e report, 2005)
The volume collects the contributions presented at the XVII national congress of AIMETA. The contributions are grouped according to the various sectors of theoretical and applied mechanics and are offered by a vast scientific community. In addition to the classical sectors, themes of interdisciplinary significance and of considerable interest and highly innovative content were added, for the analysis of which small exchange symposia were proposed. Organised according to 52 sessions (plenary and parallel), the volume contains 290 scientific works that are mainly the result of international cooperation. Therefore, the work represents a significant picture of the current situation and future prospects for mechanics.